2008
DOI: 10.1210/en.2007-1724
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Prouroguanylin Is Processed to Its Active Natriuretic Form Exclusively within the Renal Tubules

Abstract: The intestine and kidney are linked by a mechanism that increases salt excretion in response to salt intake. The peptide uroguanylin (UGn) is thought to mediate this signaling axis. Therefore, it was surprising to find (as reported in a companion publication) that UGn is stored in the intestine and circulates in the plasma almost exclusively in the form of its biologically inactive propeptide precursor, prouroguanylin (proUGn), and, furthermore, that infused proUGn leads to natriuretic activity. Here, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 69 publications
(97 reference statements)
5
43
0
Order By: Relevance
“…CCK and PYY were obtained from Phoenix Pharmaceuticals Inc. Prouroguanylin and proguanylin were obtained from BioVendor R&D. Exendin-4 was obtained from California Peptide Research Inc. The prouroguanylin antiserum (antibody 6910) was provided by Michael Goy (University of North Carolina, Chapel Hill, North Carolina, USA) (51).…”
Section: Methodsmentioning
confidence: 99%
“…CCK and PYY were obtained from Phoenix Pharmaceuticals Inc. Prouroguanylin and proguanylin were obtained from BioVendor R&D. Exendin-4 was obtained from California Peptide Research Inc. The prouroguanylin antiserum (antibody 6910) was provided by Michael Goy (University of North Carolina, Chapel Hill, North Carolina, USA) (51).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Ugn knockout mice are hypertensive compared with wild-type controls and show an impaired natriuretic response to increased oral salt intake, whereas Gn knockout mice have normal blood pressures and sodium balance (10,31). Thus, Ugn has been credited with a regulatory role in sodium balance that is triggered by alterations in dietary salt intake per se, thereby differing from other sodium regulatory systems that respond to the subsequent changes in extracellular volume and arterial pressure (16,41).…”
mentioning
confidence: 99%
“…Metabolic tracer studies reveal that proUgn is not converted to Ugn within the circulation, even after 60 min of infusion; instead, several metabolites of proUgn, including Ugn, are produced within the kidney and are excreted in urine (41). One or more of these metabolites, but principally the 15 amino acid form of Ugn (Ugn-15), has been presumed to be the active agent that is responsible for the natriuresis produced by this enterorenal endocrine axis (17,36,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Qian and colleagues (44) demonstrated that the conversion of prouroguanylin to UGN occurs within the lumen of renal tubules.…”
mentioning
confidence: 99%